Longitudinal mode-filling to cancel SBS in fully-fibered MOPAs dedicated to the production of high-energy nanosecond pulses - Jolly A.; Gokhan F.S.; Bello R.; Dupriez P. (SPIE, 2014)
We present a comprehensive experimental study of the technique of Longitudinal Mode Filling (LMF) applied to the reduction of Stimulated Brillouin Scattering (SBS), in Ytterbium Doped Fibre Amplifiers (YDFA) at the wavelength of 1064 nm. Pulse durations and Mode Field Diameters (MFD) lie in the ranges of 10 - 100 ns and 10 - 35 ?m, respectively. Input pulse-shaping is implemented by means of direct current modulation in multimode Laser-Diode seeds. This evidences a number of interests in the development of robust and low cost Master Oscillator Power Amplifiers (MOPA). Highly energetic, but properly shaped, nanosecond pulses may be produced this way without any need of additional electro-optical means for in-line phase and amplitude modulation. Seeds consist of Distributed Feed- Back (DFB) and Fibre Bragg Gratings (FBG) with different fibre lengths. We demonstrate the benefit of LMF with properly controlled mode spacing, in combination with chirp effects due to fast current transients in the semiconductors, in order to deal with SBS thresholds in the range of a few to some hundred ?J. The variations of the SBS threshold are discussed versus the number of longitudinal modes, the operating conditions of the selected seed and pulse-shaping conditions. © 2015 SPIE.
Brussels Photonics Team (B-PHOT);Brussels-Capital Region;Fonds Wetenschappelijk Onderzoek (FWO);The Society of Photo-Optical Instrumentation Engineers (SPIE);Ville de Bruxelles
Nonlinear Optics and Its Applications VIII; and Quantum Optics III -- 14 April 2014 through 16 April 2014 -- -- 110770
Keywords: SBS; YDFA